Experimental and Numerical Simulation of Hot Embossing for Fabrication of Glass Microlens Array - Lee, Helen May Shian; Syarifah Nur Hasanah, Syed Kamarudin; Mohd Zairulnizam, Mohd Zawawi (IEEE, 2022)
In this work, a hot embossing process for replication of glass microlens array (MLA) on optical glass substrate is proposed. Both numerical simulation and experimental validation were employed to investigate the filling behavior of the glass material into the microstructure mold cavities. The finite element method (FEM) was carried out using Ansys software after the establishment of the model layout and boundary condition. For validation, the K-PG375 optical glass samples were pressed at a temperature above the glass transition temperature Tg, using a home-made hot embossing setup. Then, the correlation between two- dimensional (2D) FEM analysis and experiments were established, which provide a guideline for understanding of the glass filling behavior in the viscoelastic region. The replication quality of the embossed glass was confirmed using scanning electron microscopy (SEM) and atomic force microscope (AFM). Overall, the simulation result gave a very useful insight to predict the optimum processing condition for the thermal replication process primarily the temperature, pressure and holding time.